1972
DOI: 10.1038/bjc.1972.61
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism in Hodgkin's Disease

Abstract: An evaluation of iron metabolism has been carried out in 23 untreated patients with Hodgkin's disease and 6 patients with other lymphomata. The reduction in red cell life span is related to the stage of the disease. There is an almost universal impairment of iron release from the reticuloendothelial system with a consequent sideropenia and failure of iron delivery to the bone marrow for erythropoiesis. This defect is found in all stages of the disease and is not related to systemic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Serum iron levels gradually increase towards its normal value as the clinical state improves. Similarly, in a group of patients with Hodgkin's disease, the fall of serum iron levels correlates with the severity and extent of disease ranging from mean values of 16.4, 11.4, 8.6, and 6.9 uM for stages 1, 2, 3, and 4 respectively [32]. A consistent finding in patients with malignant neoplasms is that hypoferremia increases as their clinical condition deteriorates and subsides during periods of remission [33].…”
Section: The Hypoferremic Responsementioning
confidence: 84%
“…Serum iron levels gradually increase towards its normal value as the clinical state improves. Similarly, in a group of patients with Hodgkin's disease, the fall of serum iron levels correlates with the severity and extent of disease ranging from mean values of 16.4, 11.4, 8.6, and 6.9 uM for stages 1, 2, 3, and 4 respectively [32]. A consistent finding in patients with malignant neoplasms is that hypoferremia increases as their clinical condition deteriorates and subsides during periods of remission [33].…”
Section: The Hypoferremic Responsementioning
confidence: 84%
“…A direct correlation has been shown between the extent of disease and decreases in the saturation of transferrin in patients with Hodgkin's disease [167]. Although the uptake of nutrients may vary between normal and malignant cells an increased storage of iron has not generally been demonstrated: in fact, the iron content of certain tumours (e.g.…”
Section: Ironmentioning
confidence: 99%
“…De Sousa et al (1977 have reported poor proliferative responses to phytohaemaglutinin (PHA) of peripheral blood lymphocytes from patients with HD when compared with normal controls, corrected by splenectomy. This data coupled with observations of increased T-cell percentages in the spleens from patients with HD (Kaur et al, 1974;Payne et al, 1976;Gupta, 1980) led De Sousa et al (1977 to postulate that depressed cell immunity in the blood is a consequence of the sequestration of a particular T-cell subset in the spleen and further to suggest that this may be associated with the presence of iron binding proteins (IBP) in the cells of the reticuloendothelial system (De Sousa et al, 1978 Anomalies of iron handling by the phagocytic system in HD were first described by Beamish et al (1972). De Sousa et al (1977 examined iron deposition and the distribution of IBP in five spleens involved with the disease and one nonHodgkin's lymphoma control.…”
mentioning
confidence: 99%
“…Anomalies of iron handling by the phagocytic system in HD were first described by Beamish et al (1972). De Sousa et al (1977) examined iron deposition and the distribution of IBP in five spleens involved with the disease and one nonHodgkin's lymphoma control.…”
mentioning
confidence: 99%